Effects and Safety of Linagliptin as an Add-on Therapy in Advanced-Stage Diabetic Nephropathy Patients Taking Renin-Angiotensin-Aldosterone System Blockers - Yuichiro Ueda; Hiroki Ishii; Taisuke Kitano; Mitsutoshi Shindo; Haruhisa Miyazawa; Kiyonori Ito; Keiji Hirai; Yoshio Kaku; Honami Mori; Taro Hoshino; Susumu Ookawara; Masafumi Kakei; et al. (AboutScience Srl, 2016)
Background We investigated the effects and safety of linagliptin as an add-on therapy in patients with advanced-stage diabetic nephropathy (DMN) taking renin-angiotensin-aldosterone system (RAAS) blockers. Method Twenty advanced-stage DMN patients (estimated glomerular filtration rate (eGFR): 24.5 ± 13.4 mL/min/1.73 m 2 ) taking RAAS blockers were administered 5 mg/day linagliptin for 52 weeks. Changes in glucose and lipid metabolism and renal function were evaluated. Results Linagliptin decreased glycosylated hemoglobin levels (from 7.32 ± 0.77% to 6.85 ± 0.87%, P < 0.05) without changing fasting blood glucose levels, and significantly decreased total cholesterol levels (from 189.6 ± 49.0 to 170.2 ± 39.2 mg/dL, P < 0.05) and low-density lipoprotein cholesterol levels (from 107.1 ± 32.4 to 90.2 ± 31.0 mg/dL, P < 0.05) without changing high-density lipoprotein cholesterol and triglyceride levels. Urine protein/creatinine ratio and annual change in eGFR remained unchanged. No adverse effects were observed. Conclusion Linagliptin as an add-on therapy had beneficial effects on glucose and lipid metabolism without impairment of renal function, and did not have any adverse effects in this population of patients with advanced-stage DMN taking RAAS blockers.